Perancangan Kriptografi Block Cipher berbasis Pola Dribbling Practice - Theophilus Wellem; Rizky Restu Fauzi (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2021)
Block cipher is a technique in modern cryptography used to encrypt/decrypt digital data by dividing messages into data blocks and then encrypting or decrypting the data on a block-by-block basis. This study aims to design a block cipher based on a dribbling practice pattern as a new variation of existing block ciphers. The principles of block cipher design, such as substitution box, XOR operation, Feistel network, and key transposition, are applied in designing this block cipher. The avalanche effect (AE) value and the correlation value between plaintext and ciphertext are used as the metrics in evaluating the designed block cipher. The testing results show that an AE value of 54.687% is achieved when a character in the input plaintext changes. Therefore, there are significant changes in the resulting ciphertext when the input plaintext is slightly changed. Furthermore, the correlation value between plaintext and ciphertext is 0.247 (low correlation). As a result, it is hard to obtain the plaintext back based on the ciphertext result. These values are better compared to some previous studies available.